ADAPTASI FONT HURUF LATIN DARI KARAKTER VISUAL TIPOGRAFI AKSARA MAKASSAR ‘LONTARA’ - Brahma, Adhreza (Visualita Jurnal Online Desain Komunikasi Visual, 2017)
Characters are the part of the culture that determines the level of human thinking as well as the characteristics and identity of an ethnic. In this modern era, communication in Indonesia generally always using the Latin letters with the aim to be used universally. The results of this study are refers to the visual identification of the fonts 'Angled' which is an innovation of the writing system, that used by the predecessors of Makassar tribes, starting from anatomical structures, visual characteristics, and geometric element studies to be applied as a new form in digital typeface from Lontara characters into Latin script (Roman).